VALUE CHAIN ANALYSIS OF BROILER TO INCREASE COMPETITIVENESS (Case Study at PT. Charoen Pokphand Indonesia, Tbk) - Surip Prayugo; Arief Daryanto; Setiadi Djohar (School of Business, Bogor Agricultural University (SB-IPB), 2012)
The objectives of this research are to (1) map the value chain in broiler at PT. Charoen Pokphand Indonesia, Tbk (CPI); (2) analyze the value chain governance in broiler at CPI; (3) analyze the margin of marketing at broiler industry both on farm or off farm; (3) analyze the gap between the expectation and the performance of consumers (farmers) upon using products of CPI and (4) recognize factors influencing competitiveness in broiler industry; and (5) to formulate strategy for value chain upgrading at CPI in order to increase competitiveness of broiler. As revealed by the value chain analysis, the role of CPI in this value chain is highly significant. All poultry inputs (DOC, feed, veterinary medicine, and poultry equipments) are supplied by CPI. As for downstream sector, CPI processes broiler into its derivatives. The type of value chain governance between feed supplier, DOC, and veterinary medicine, poultry equipment, and poultry derivates belongs to market value chain. Whereas the type of value chain governance between carcass supplier and restaurant belongs to captive value chain. Based on the margin of marketing analysis, the party that gains the lowest margin is farmer and the party that receives the highest margin is the processor. In gap analysis, the lowest attribute of competitiveness is the feed spending and the highest attribute is the spending on veterinary medicine for two months. Factors that influence the competitiveness in poultry industry are condition, demand, industry competition, main industries and supporting industries, and government’s role.Keywords: Value Chain, Competitiveness, Broiler, PT. Charoen Pokphand Indonesia, Tbk, Margin of Marketing Analysis, Gap Analysis, SWOT Analysis